Transformation Scoring System (TSS): A new assessment index for clinical transformation of follicular lymphoma. (6th October 2020) - Shichijo, Takafumi; Maruyama, Dai; Yamauchi, Nobuhiko; Maeshima, Akiko Miyagi; Sugano, Masato; Yuda, Sayako; Tajima, Kinuko; Kurihara, Hiroaki; Shimada, Kaoru; Suzuki, Tomotaka; Toyoda, Kosuke; Makita, Shinichi; et al.
Abstract: Although histologic analysis is the gold standard for diagnosing follicular lymphoma (FL) transformation, many patients are diagnosed with transformation by clinical factors as biopsy specimens often cannot be obtained. Despite the frequency of clinical diagnosis, no clinical assessment tool has yet been established for FL transformation in the rituximab era. We derived and validated a transformation scoring system (TSS) based on retrospective analyses of 126 patients with biopsy‐proven FL and histologic transformation (HT) at two hospitals of the National Cancer Center of Japan. In the derivation set (76 patients), the detailed analyses of the clinical characteristics at disease progression showed that lactate dehydrogenase (LDH) elevation, focal lymph nodal (LN) enlargement, hemoglobin <12 g/dl, and poor performance status (PS) (2‐4) were associated with HT. The weights of these variables were decided based on the regression coefficients. Next, we constructed a TSS encompassing the above four factors: LDH, (> upper limit of normal [ULN], ≤ULN ×2) (1 point), (≥ULN ×2) (2 points); focal LN enlargement, (≥3 cm, <7 cm) (1 point), (≥7 cm) (2 points); hemoglobin <12 g/dl (1 point); poor PS (2 points). We identified a high positive predictive value (PPV) (96.4%) and negative predictive value (NPV) (85.4%) for diagnosing HT when a cutoff score of 2 was selected for our TSS. In an external validation set (50 patients), the probability of HT was high with scores ≥2 (PPV, 93.3%; NPV, 82.9%). We developed a TSS that offers a simple, yet, valuable tool, for diagnosing HT, especially in patients who cannot undergo biopsy. Abstract : We developed a new transformation scoring system (TSS) for determining the clinical transformation of FL and successfully validated it in an independent cohort. TSS promises to be a simple, yet valuable tool, for the diagnosis of clinical transformation in both daily practice and clinical trials, especially in patients for whom obtaining a biopsy specimen is not feasible.